Influence of mastitis on production and quality raw milk - Gustavo Lucas Costa Valente; Lohanna de Carvalho Silva (Revista do Instituto de Latícinios Cândido Tostes, 2023)
Milk is a perishable product, and its quality must be evaluated from the farm to the dairy. The legislation imposes that the main parameters to certify the quality of milk are temperature measurement; fat, protein, total solids, and non-fat contents; determinations of the cryoscopic index, relative density at 15°C and titratable acidity; research for antibiotic residues; standard plate count (SPC); and somatic cell count (SCC). One of the biggest problems faced in dairy cattle is mastitis, which consists of inflammation of the mammary gland, mainly due to bacterial contamination. This pathology causes a great economic impact on milk producers, as it changes the composition of the milk and may lead to the disposal of milk, reduces animal production, generates expenses with treatment, and may result in the disposal of animals. It is considered that to avoid mastitis and high values of SCC and SPC, it is necessary to carry out a set of management from milking to the destination of milk for the dairy industry. The main objective of the review was to discuss the impacts of the mastitis on production and quality of raw milk. Studies indicate the existence of a negative correlation between SCC and the volume of milk produced. In addition, milk with high CCS shows changes in composition, such as a reduction in solids content and in the casein/whey protein ratio. Therefore, it was possible to conclude that mastitis interferes negatively with the production and quality of milk, highlighting the need to prevent its occurrence and identify, isolate, and treat affected animals.